Peran Rentenir terhadap Pembiayaan pada Para Pelaku Usaha Mikro di Masa Pandemi COVID-19 Tahun 2020-2021 (Studi Kasus di Pasar Pon Jombang) - Soenjoto, Wening Purbatin Palupi; Juwita, Dwi Runjani (Institut Agama Islam Negeri Ponorogo, 2022)
Micro business actors in Indonesia are the largest business actors compared to small, medium, and large business actors. The distribution and diversity of products sold by micro business actors is more evenly distributed to remote villages. These micro business actors meet the needs of the middle-to-middle class people. down with sales transactions that rely more on direct transactions and the use of cash in trade. But what happens in the reality of trading is precisely these micro actors who are still very minimally touched by financing by banks. The application of banking policies and the administration system in the banking financing process makes it difficult for players micro-enterprises. Thus, micro-enterprises prefer to finance loan sharks, although in terms of loan interest rates are higher than banks. Ease of disbursing financing faster without the need for collateral as a financing requirement is the reason most recognized by micro-business actors who do financing to moneylenders. This study uses a qualitative research method causal (explanatory) case studies to determine the role of moneylenders in financing micro-enterprises and explain descriptively why micro-entrepreneurs prefer to finance loan sharks rather than banks. This study focuses on Micro-business actors, the majority of whom are financing loan sharks and the development of moneylenders, are changing, more